2018
DOI: 10.1190/tle37050372.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of temperature dependency of elastic moduli in heavy oil deposits

Abstract: Seismic monitoring of oil sands during hot or cold production requires a valid rock physics model. The effective elastic properties of heavy oil deposits depend on temperature variations, which consequently alter the P- and S-wave velocities in thermal recovery processes. The authors discuss the relationship between temperature, apparent shear modulus, frequency, and velocity dispersion. We use log data from wells drilled in heated and cold zones of a bitumen reservoir to calculate bulk and shear moduli along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Wang and Nur tested the wave velocities in hydrocarbon‐saturated rocks and concluded that the largest changes in velocities with temperature are associated with the melting of solid hydrocarbons in rocks just like oil sands. Javanbakhti et al discuss the relationship between temperature, apparent shear modulus, frequency, and velocity dispersion, and they used a linear relationship to model bulk modulus decline with temperature. Neither the static nor ultrasonic experiments can express the elastic properties as a continuous function of temperature, because of few test data and poor homogeneity among different samples.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Nur tested the wave velocities in hydrocarbon‐saturated rocks and concluded that the largest changes in velocities with temperature are associated with the melting of solid hydrocarbons in rocks just like oil sands. Javanbakhti et al discuss the relationship between temperature, apparent shear modulus, frequency, and velocity dispersion, and they used a linear relationship to model bulk modulus decline with temperature. Neither the static nor ultrasonic experiments can express the elastic properties as a continuous function of temperature, because of few test data and poor homogeneity among different samples.…”
Section: Introductionmentioning
confidence: 99%